Structural Analysis of Formation the Professional and Practical Training of Future Translators in the Information and Computing Environment - Dolynskyi, Yevhen (Pedagogical Discourse, 2015)
The modernization of higher education in Ukraine is caused by processes occurring in the European territory. It actualizes the need for training of human to the life in the information society. The expansion and revival of international political, economic and cultural relations with countries of near and far abroad substantially increases the importance of translators who are the first to represent our country in the international arena, its powerful scientific and technical potential, rich history and culture. The activation of European and global integration to the educational environment indicates the importance to find new more sophisticated approaches and technologies of training the translators that would ensure the achievement of good results and also it increases the necessity to focus on various aspects of their trainings. In order to better understand the features of professional training of students-interpreters we should consider the nature and importance of this concept. In general the term «profession» is defined as the specialty, a type of work, an occupation that requires some training and is the primary meaning of existence. Today it is almost impossible to imagine educational process without the use of information technologies and learning tools. Examining the essence of informative training, the use of information and computer technologies in professional training, it is defined the components that allow examine its effectiveness in future translators and to establish criteria and indicators for assessing the information readiness for studying of disciplines from professional and practical training cycle in the university information and computing environment.